SAT0264 A Single Centre Experience of Childhood Polyarteritis Nodosa from North India. (15th July 2016) - Kumar, A.; Gupta, A.; Singhal, M.; Gupta, A.; Nada, R.; Minz, R.W.; Suri, D.; Singh, S.
Abstract : Background: Polyarteritis nodosa (PAN) is a necrotizing vasculitis involving medium or small sized vessels. It is characterized by a variable clinical presentation, ranging from a benign cutaneous involvement to a more severe systemic disease with multisystem involvement Objectives: We describe clinical and laboratory features, treatment and outcome of pediatric PAN patients Methods: A retrospective case review of all children diagnosed as PAN at a single tertiary care hospital in north India between 1990 to 2014 was done. Diagnosis of PAN was based on European League against Rheumatism (EULAR)/Paediatric Rheumatology European Society (PRES)/Paediatric Rheumatology International Trials Organisation (PRINTO) classification criteria. (1) Results: A total of 16 children (12 boys and 4 girls) with PAN were identified. Median age of symptom onset and diagnosis was 8 years (range 1–11 years) and 9 years, respectively. The presenting symptoms were fever (68%), CNS complaints [headache, seizures, altered sensorium, stroke or vision loss] (50%), fatigue (44%), myalgia (44%), gangrene (31%), weight loss (31%), gastrointestinal complaints [pain abdomen, bleed] (31%) and bluish black patches over body (19%). Hypertension was present in 88% patients at admission. Various neurological manifestations were seen in 62.5% patients. Skin involvement (digital gangrene, livedo reticularis, bluish black patches, erythema nodosum or necrotic ulcer) was seen in 50% patients. Renal and gastrointestinal involvements were seen in 38% patients each. CT angiography was done in 13 patients. Aneurysmal dilatation of vessels was seen in 6 patients, while 3 patients showed features of renal infarcts. CT angiography was normal in 4 patients. In 2 such patients, digital subtraction angiography (DSA) showed aneurysmal dilatation of vessels. ANCA was positive in 4 patients (c-ANCA in 3 and p-ANCA in 1). HBsAg was positive in 3 patients (not treated as liver function remained normal). ASO was positive in 4 patients (2 patients were given penicillin; one patient had a relapse with high ASO titres on stopping penicillin). Two patients had only a single visit to the clinic; hence their treatment details were not available. Treatment regimen included cyclophosphamide (78%), methylprednisolone pulses (43%), oral prednisolone (93%), maintenance azathioprine (36%), and IVIg and methotrexate (14% each). Mean follow up was for 4.8 years (range 0–25 years). Five patients experienced relapses with more than 1 relapses seen in 2 patients. Relapses were noted as early as 6 months and as late as 22 years after diagnosis Conclusions: We found a significant male preponderance in our cohort. Streptococcal infection can have a pathogenic role in the disease progression and relapse, and penicillin prophylaxis can prevent disease relapse in susceptible patients References: Ozen S, Pistorio A, Iusan SM, Bakkaloglu A, Herlin T, Brik R, et al. EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part II: Final classification criteria. Ann Rheum Dis. 2010 May;69(5):798–806. Disclosure of Interest: None declared